2017
DOI: 10.1104/pp.17.01583
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Root Secondary Growth as a Strategy for Phosphorus Acquisition

Abstract: We tested the hypothesis that reduced root secondary growth of dicotyledonous species improves phosphorus acquisition. Functional-structural modeling in SimRoot indicates that, in common bean (Phaseolus vulgaris), reduced root secondary growth reduces root metabolic costs, increases root length, improves phosphorus capture, and increases shoot biomass in lowphosphorus soil. Observations from the field and greenhouse confirm that, under phosphorus stress, resource allocation is shifted from secondary to primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 51 publications
3
88
3
Order By: Relevance
“…These results have recently been supported by empirical results with maize, which show that genotypes with greater RCA formation have greater topsoil foraging, P capture, growth, and yield in low‐P soil than genotypes with less RCA, notwithstanding the reduction in mycorrhizal habitat by RCA formation (Galindo‐Castañeda et al ., ). In dicots, P stress inhibits the secondary growth of roots, and common bean genotypes with greater inhibition of secondary growth under P stress have reduced root costs, greater P capture, and greater growth in low‐P soil (Strock et al ., ; Fig. ).…”
Section: Phosphorusmentioning
confidence: 93%
See 2 more Smart Citations
“…These results have recently been supported by empirical results with maize, which show that genotypes with greater RCA formation have greater topsoil foraging, P capture, growth, and yield in low‐P soil than genotypes with less RCA, notwithstanding the reduction in mycorrhizal habitat by RCA formation (Galindo‐Castañeda et al ., ). In dicots, P stress inhibits the secondary growth of roots, and common bean genotypes with greater inhibition of secondary growth under P stress have reduced root costs, greater P capture, and greater growth in low‐P soil (Strock et al ., ; Fig. ).…”
Section: Phosphorusmentioning
confidence: 93%
“…Crop breeding for root architectural and anatomical phenotypes with better P capture could have important indirect consequences for AMS, however. For example, RCA formation, root cortical senescence, and reduced secondary growth all improve P capture, and all have important consequences for AMS by regulating the volume of AMS habitat in the root cortex (Galindo‐Castañeda et al ., ; Schneider & Lynch, ; Strock et al ., ). Architectural phenes that localize root foraging in shallow or deep soil domains may also affect AMS, since the propagules of fungal symbionts, as well as the foraging environments of extraradical hyphae, are more favorable in the topsoil (Lynch & Wojciechowski, ).…”
Section: Phosphorusmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, enhanced carbohydrate transport to the root has been demonstrated for nitrogen (N) and phosphorus (P) limitation (Hermans et al ). In the case of P limitation in common bean ( Phaseolus vulgaris ), it has been recently confirmed that secondary root growth is impaired in favor of root elongation, thus optimizing P acquisition under low P conditions (Strock et al ). This preferential C investment in primary root growth was also reported for Arabidopsis submitted to low Pi (Hanlon et al ).…”
Section: Root Sugar Transport In Response To Abiotic Factorsmentioning
confidence: 99%
“…Lynch () and Strock et al . () have reported that smaller root cross‐sectional area induced by plants adaptive response of decreased root secondary growth increases root length (for greater soil exploration) and improves the consumption of growth‐limiting resources. Growth allometry is induced by multiple cryptic genetic factors associated with local climate and abiotic stress response (Vasseur et al ., ), suggesting that the contrasting response of tiller and main‐shoot nodal roots may be an adaptive response to water deficit.…”
Section: Discussionmentioning
confidence: 99%